The Effect of Computer Assisted Learning on Student Mathematics Learning Outcomes - Mashuda Mashuda (Universitas Islam Jember, 2019)
Learning is the main activity of the education process. The researcher compared the results of students' mathematics learning between students who were taught by conventional learning and used computer-assisted learning in learning. Based on the results of data analysis it is known that from dk 1 and significant level of 0.05 then the price of chi squared count> table (1538> 3.841), it can be concluded that Ha is accepted and Ho is rejected. In this case based on the results of the research we can say that computer-assisted learning has a significant effect on the student mathematics learning outcomes. The teacher must always give motivation to the students to be understand the material taught and cooperation and responsibility for the success of a learning process. Keyword: computer assisted learning and mathematic learning outcomes.